Serologic detection of vaccine associate IgG responses in horses using a multiplex magnetic microsphere assay - Haukos, Kaitlin A. (Kansas State University, 2017)
To protect horses from disease, equine practitioners typically prescribe a protocol of an initial primary vaccination followed by a booster vaccination 3-4 weeks later. Subsequent boosters are given every 6-12 months depending on the pathogen of concern. Each vaccination incurs an additional cost and increased chance for adverse reactions. Despite wide-spread protocol acceptance, duration of effectiveness of vaccines in protecting horses from disease is not well documented. It was hypothesized that horses vaccinated annually since birth have increased antibody production that remains consistent and sufficient for long-term protection from common diseases. This work resulted in the development of a novel, multiplex-magnetic bead-based indirect immunoassay to screen sera from vaccinated adult horses to measure antibody levels in response to vaccine administration. Antigens tested included West Nile Virus, Eastern Equine Encephalitis, Western Equine Encephalitis, Equine Influenza Virus, Equine Herpes Virus 1 and 4, Tetanus, and 7 different Rabies antigens (3 lab and 4 wild strains). The developed assay was a 7-plex capture antibody, which quantified equine IgG (Immunoglobulin G) that binds viral antigens derived from different rabies virus strains along with pure vaccine samples of the 7 different antigens. A 7-point standard curve was developed to quantify the viral-antigen reactive IgG concentration in vaccinated horse serum. Vaccinated horses increased serum antibody concentration for each antigen post-vaccination with the percent increase ranging between 34.0% for Equine Herpes Virus 4 and 257.3% for Equine Influenza Virus. Use of the novel assay will provide equine veterinarians with an economical method to measure immune activation toward common pathogens of concern. This methodology will provide foundation level information regarding antigen specific IgG concentrations that ultimately may be extrapolated to establish protective levels of immunity resulting in establishment of vaccine protocols.
Keywords: Equine; IgG; Vaccine reaction; Microsphere Assay; Serology